The relationship between immigration, labour market conditions and GDP: Evidence from the states of the USA - Ozcan, Burcu (Inderscience Publishers, 2020)
This study aims at analysing the relationship between immigration, unemployment, wage and income in the 15 host states in the USA that receive the most immigrants. The bootstrap panel Granger causality test developed by Konya (2006) is employed over the period of 1990-2016. The results indicate that immigration aggravates the unemployment level in the domestic labour market in the seven most populated host states, whereas it has no significant impact on the unemployment level in the remaining eight states. Based on these results, some crucial policy implications could be suggested. © 2020 Inderscience Enterprises Ltd.
Keywords: Complementarity; Demand-side effects; Immigration; Income; Labour market; Native workers; Panel causality test; Substitution; Supply-side effects; Unemployment; USA; Wage